Pengelolaan Dana Desa dan Evaluasi: (Studi Kasus terhadap Pengelolaan Dana Desa di Desa Sungai Abu Kecamatan Air Hangat Timur Kabupaten Kerinci) - Kafrini Kafrini; Asrinaldi Asrinaldi; Tengku Rika Valentina (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Village funds are funds sourced from the APBN which are managed autonomously by each village in order to create a more independent village. In accountability for the use of village funds, the village government is required to be able to carry out in accordance with the regulations governing the use of village funds. The purpose of this research is to find out what is the role of the Village Elite in managing village funds, and what problems are faced in managing village funds in 2020. This study uses qualitative research with case studies. Data collection techniques were carried out by interviewing and documenting and then comparing the interview data with secondary research data. Data analysis used descriptive evaluative analysis with three steps in the form of data reduction, data presentation, and drawing conclusions. The results of this study indicate that in the process of managing village funds in Sungai Abu Village, Air Hangat Timur District, there are obstacles, including the weak capacity and capability of village government human resources, lack of innovation in program activities and low community participation. So this still affects the village's ability to manage village funds.